Selenization of CuInS2 by rapid thermal processing – an alternative approach to induce a band gap grading in chalcopyrite thin-film solar cell absorbers?. Issue 5 (9th January 2019) - Félix, Roberto; Weber, Alfons; Zander, Ole; Rodriguez-Álvarez, Humberto; Schubert, Björn-Arvid; Klaer, Joachim; Wilks, Regan G.; Schock, Hans-Werner; Mainz, Roland; Bär, Marcus
Abstract : Characterization of selenium-treated CuInS2 reveals a band gap grading and a surface Cu enrichment, opening new chalcopyrite absorber tailoring opportunities. Abstract : A treatment of CuInS2 (CIS) based on rapid thermal processing (RTP) selenization is developed, aiming at tuning the absorber's band gap grading using the [Se]/([S] + [Se]) composition. X-ray photoelectron spectroscopy and X-ray fluorescence analysis measurements of RTP-treated CIS samples (with the used set of RTP-parameter ranges) show a greater treatment effect at the surface of the sample compared to the bulk. A tuning of the [Cu] : [In] : ([S] + [Se]) surface composition from a Cu-poor 1 : 3 : 5 to a 1 : 1 : 2 stoichiometry is also observed in RTP-treated CIS absorbers with lower to higher surface Se contents, respectively. Ultraviolet photoelectron spectroscopy measurements show a shift in valence band maximum toward the Fermi level, E F, in higher surface Se content samples [from (−0.88 ± 0.1) to (−0.51 ± 0.1) eV], as expected for a reduction of the (surface) band gap produced by exchanging S with Se. Ultraviolet-visible spectrophotometry reveals a reduction in the optical (bulk) band gap of samples with greater Se incorporation [from (1.47 ± 0.05) to (1.08 ± 0.05) eV], allowing for a working window for optimization purposes.